Measuring faking on five-factor personality questionnaires: the usefulness of communal and agentic management scales - Galić, Zvonimir (Array, 2013)
The aim of the study was to test whether the Agentic Management (AM) and Communal Management (CM) scales (Paulhus, 2006) represent valid indicators of faking on a Five Factor personality questionnaire. These scales represent recent advances in measurement of desirable responding. In a within-subject design study, 210 participants completed a Big Five personality questionnaire and social desirability inventory, both in honest and simulated selection conditions. Although the AM and CM scales were sensitive to situational demands and substantially correlated with the level of faking on some personality traits, our analyses revealed that they cannot be used to correct personality scales nor to eliminate participants from selection procedures.